Understanding the Presentations and Patterns of Traumatic Spinal Cord Injuries to Develop the Data Collection Format - Pal, Ranabir; Singh, Mithasha; Kumar, Kiran; Sharma, Vinay Sagar; Jahanavi, Mundlapudi; Jena, Ranjan Kumar; Munivenkatappa, Ashok; Bhandarkar, Prashant; Agrawal, Amit (Indian Journal of Neurotrauma, 2017)
Background The intensity of the damage to the nerve fibers is not measured through the severity of the spinal cord injury.Objective To understand the pattern of neurologic features in traumatic spinal cord injuries.Methods This was a case series of the total care of patients with consecutive acute spinal cord injury at different levels during the years 2015 to 2017, from extrication and transportation following the accident to death, or the completion of primary definitive rehabilitation. This work examined demographic and clinical characteristics of 220 consecutive cases of acute spinal injuries with or without neurologic symptoms subjected to conservative and surgical interventions. Age, sex, addiction patterns of smoking and alcohol, presenting symptoms, neurologic status, and postoperative outcomes are compared with the preoperative findings.Results The registry included 220 patients with spinal injury; majority in 41 to 50 years age group (28.6%) and males (77.7%). Nearly one-half had cervical (46.3%) injuries; 84.3% male; comparable proportion of dorsal and lumbar injuries had male dominance. One-fifth of the patients were smokers and alcoholics, all males. Mean hospital stay was 36.7 ± 140.5 days. Majority presented with neck pain (48.9%), radicular pain (56.4%), limb weakness (73.3%), and tingling sensation (47.7%); 14.4% reported tightness in limbs and 18.8% bladder involvement. In postoperative period, symptoms persisted in varied proportions. Significantly of postoperative neck pain was observed more among males (88.5%), yet symptoms that reduced postoperatively were neck pain, limb weakness, and tingling sensation. However, bladder involvement increased significantly.Conclusion The results showed that greater attention should be paid to older and male population that has more spinal cord injuries while comparable to those of the other studies in neurodeficits and clinical features.
Keywords: spinal injury; data collection; traumatic spinal cord injury